2021
DOI: 10.1016/j.jdermsci.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, open-label, uncontrolled, single-arm phase 2 study of tirabrutinib, an oral Bruton’s tyrosine kinase inhibitor, in pemphigus

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Preclinical data showed Dsg3 CAAR T cells specifically target and lyse Dsg3-specific B cells, thus preserving non-pathogenic B cells ( 78 ). Rilzabrutinib and tirabrutinib, oral Bruton’s tyrosine kinase inhibitors that inhibit B-cell activation, were found to decrease the dose of systemic corticosteroid needed and reduce disease activity in pemphigus vulgaris in a phase 2 trial ( 79 80 ). In addition, efgartigimod and ALXN1830, FcRn blocking antibodies, showed an early onset of clinical improvement in pemphigus patients in phase 2 trials ( 81 82 ).…”
Section: Autoimmune Bullous Diseasesmentioning
confidence: 99%
“…Preclinical data showed Dsg3 CAAR T cells specifically target and lyse Dsg3-specific B cells, thus preserving non-pathogenic B cells ( 78 ). Rilzabrutinib and tirabrutinib, oral Bruton’s tyrosine kinase inhibitors that inhibit B-cell activation, were found to decrease the dose of systemic corticosteroid needed and reduce disease activity in pemphigus vulgaris in a phase 2 trial ( 79 80 ). In addition, efgartigimod and ALXN1830, FcRn blocking antibodies, showed an early onset of clinical improvement in pemphigus patients in phase 2 trials ( 81 82 ).…”
Section: Autoimmune Bullous Diseasesmentioning
confidence: 99%
“…Tirabrutinib hydrochloride (ONO/GS-4059), also known as tirabrutinib, is a broad-range oral BTK inhibitor, which has recently been licensed in Japan for the treatment of plasma cell lymphoma, primary lymphoma of the central nervous system, and Waldenstrom macroglobulinemia [ 3 ]. Tirabrutinib inhibits increase in culprit protein levels in lupus-prone animal and human B-cells and reduces stimulation-induced IgG production (unpublished findings) [ 47 ].…”
Section: Role Of Btk In the Treatment Of Pemphigusmentioning
confidence: 99%
“…This molecule is designed to inhibit the IgG autoantibody-mediated signaling pathway involved in the pathogenesis of pemphigus pathogenesis and provide an alternative therapy for resistant pemphigus. Yamagamia et al [ 3 ] conducted a phase II trial to evaluate the safety and efficacy of tirabrutinib in patients with refractory pemphigus. Sixteen patients were included in this study.…”
Section: Role Of Btk In the Treatment Of Pemphigusmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Jun Yamagami et al investigated the efficacy and safety of tirabrutinib, another BTK inhibitor, in patients with refractory pemphigus in a multicenter, open-label, uncontrolled, single-arm phase II study. They reported that treatment with tirabrutinib enabled remission and reduced oral corticosteroids over time without significant safety concerns in patients with refractory pemphigus ( 57 ). Interestingly, another BTK inhibitor (PRN473) has been reported with a good response in canine pemphigus foliaceus (PF) ( 58 ).…”
Section: Therapeutics Targeting B Cells and B Cell Activationmentioning
confidence: 99%